On the Exchange Rate and Economic Policy Uncertainty Nexus: A Panel VAR Approach for Emerging Markets - Abir Abid; Christophe Rault (Center for Economic Studies and ifo Institute (CESifo), 2020)
We examine the Exchange Rate Volatility (ERV) response to the Economic Policy Uncertainty (EPU) shocks from a panel VAR perspective used for the first time in this context. Focusing on Emerging Market Economies (EME), our noteworthy findings postulate that (a) both home and foreign EPU shocks are highly significant in explaining the ERV, (b) the contribution of the foreign EPU to the ERV fluctuation overcomes the local EPU's share, (c) the ERV acts as a significant transmission channel of the US-EPU to the economic activity, (d) the home EPU increases with higher US-EPU and vice versa and (e) the latter is surprisingly and markedly sensitive to EME macroeconomic conditions. Our findings are robust to different sensitivity analyses, provide novel insights into EPU international spillovers, and have interesting policy implications for EME decisions makers and investors.
Keywords: G15; E44; C22; 330; emerging markets; economic policy uncertainty; exchange rates volatility; panel VAR